Firefly wedding. 3 - Tachibana, Oreco (Shojo beat manga., 2025)
"Satoko dreams of marrying a noble but can't escape the assassin who has her within his sights. Afflicted with a heart condition, Meiji-era noblewoman Satoko is determined to secure a marriage that will benefit her family before she dies. But before she can realize her goal, she's targeted by a mysterious assassin named Shinpei. In a last-ditch effort to save her life, Satoko asks her would-be murderer to marry her. Her proposal isn't sincere, but unfortunately for her, Shinpei loves as intensely as he kills. Can Satoko find a way to break the engagement without losing her life? Having narrowly escaped a crisis at the island brothel, Satoko and Shinpei now attempt a secret escape on a small boat. Satoko tries to explain to Shinpei that marrying a man her father approves of to help her family is more important to her than love, but Shinpei keeps insisting that he wants to marry her no matter what. As they draw closer to the mainland, they open up to each other, revealing their true feelings. However, a looming threat is closing in!"--Publisher.